The social and economic burden of retinopathy of prematurity: screening, treatment, and health policy perspectives in a transnational narrative review - Maria Ester Canepa; Massimiliano Serafino; Pasquale Striano; Luca A. Ramenghi (Frontiers in Pediatrics, 2026)
Retinopathy of prematurity (ROP) is a leading preventable cause of childhood blindness, particularly among premature infants. This transnational narrative review synthesizes international evidence on the economic and social burden of ROP from 2003 to 2025, focusing on the cost-effectiveness of screening, diagnostic imaging, and treatment strategies. A structured PubMed search using the terms “ROP neonate social cost” and “economic impact of ROP” was supplemented through the “Similar Articles” and “Cited Articles” functions. The review included cost-effectiveness analyses, cost-utility studies, burden-of-disease reports, and policy-related evidence published in all languages. Following the thematic framework proposed by Rivero-Arias et al. (2024), the evidence was synthesized to explore the economic implications of ROP screening and management while informing future policy directions. Evidence from 15 eligible studies identified through the primary search was complemented by 71 additional relevant publications identified through PubMed citation tracking. The available evidence suggests that AI-assisted telescreening and smartphone-based imaging may represent cost-effective and scalable screening strategies, while mobile screening units and national telemedicine networks appear feasible in low- and middle-income countries. The reviewed literature also indicates that the long-term societal costs associated with ROP-related blindness substantially exceed those of timely screening and early intervention. However, important evidence gaps remain regarding long-term follow-up costs, the comparative cost-effectiveness of anti-vascular endothelial growth factor therapy vs. laser photocoagulation, and the economic consequences of delayed or missed screening. Successful ROP care models involve multisectoral collaboration among healthcare systems, education, and technology stakeholders. National initiatives in Argentina, India, Rwanda, and Saudi Arabia illustrate how integrated screening programmes, digital innovation, and international collaboration may reduce preventable ROP-related blindness while improving equitable access to care. From a policy perspective, healthcare systems should consider prioritizing screening programmes, validated telemedicine and AI-assisted technologies, national screening registries, and workforce training through tele-education. Future research should expand societal cost and cost-effectiveness analyses, particularly in high-income countries, strengthen AI validation studies, and develop country-specific economic models reflecting local healthcare resources and neonatal intensive care unit organization. Adaptive screening policies, supported by interdisciplinary collaboration and regular updates of screening guidelines, will be essential to reducing the long-term social and economic burden of ROP.